Republic of Croatia : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 1998)
This Selected Issues paper and Statistical Appendix analyzes developments in Croatia's banking sector since independence in 1991, focusing on the effects of independence, war, transition, and the bank rehabilitation process. Changes in market structure, concentration, and ownership, as well as financial performance are highlighted. The paper reviews the current legal environment governing banking operations and improvements needed to strengthen the legislative framework. Some forward-looking conclusions are presented. The paper also examines selected aspects of Croatia's export performance.